2013
DOI: 10.1038/labinvest.2013.6
|View full text |Cite
|
Sign up to set email alerts
|

PI3K p110γ overexpression in idiopathic pulmonary fibrosis lung tissue and fibroblast cells: in vitro effects of its inhibition

Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive fibroproliferative disease whose molecular pathogenesis remains unclear. In a recent paper, we demonstrated a key role for the PI3K pathway in both proliferation and differentiation into myofibroblasts of normal human lung fibroblasts treated with TGF-β. In this research, we assessed the expression of class I PI3K p110 isoforms in IPF lung tissue as well as in tissue-derived fibroblast cell lines. Moreover, we investigated the in vitro effects of the selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 35 publications
0
77
0
Order By: Relevance
“…Furthermore, both p110c pharmacological inhibition and gene silencing were able to significantly inhibit proliferation, as well as a-smooth muscle actin expression in IPF fibroblasts. These data suggest that the PI3K p110c isoform may have an important role in the pathogenesis of IPF and can be a specific pharmacological target [54]. In this regard, it has already been reported that oral administration of a p110c inhibitor significantly prevents bleomycin-induced pulmonary fibrosis in rats [55].…”
Section: Abnormal Activation Of Specific Signalling Pathways In Ipf Amentioning
confidence: 78%
“…Furthermore, both p110c pharmacological inhibition and gene silencing were able to significantly inhibit proliferation, as well as a-smooth muscle actin expression in IPF fibroblasts. These data suggest that the PI3K p110c isoform may have an important role in the pathogenesis of IPF and can be a specific pharmacological target [54]. In this regard, it has already been reported that oral administration of a p110c inhibitor significantly prevents bleomycin-induced pulmonary fibrosis in rats [55].…”
Section: Abnormal Activation Of Specific Signalling Pathways In Ipf Amentioning
confidence: 78%
“…Primary normal human lung fibroblast cell lines were established as previously described [14]. IPF lung fibroblast cell lines were established from explanted organs from IPF patients who had received a lung transplant.…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
“…qPCR was performed by using the commercially available Taqman assays for human a-SMA (ACTA2), COL-I (COL-IA1) and the housekeeping GAPDH gene (QIAGEN, Germany) following the manufacturer's instructions. Amplification conditions were identical for all genes: 94 C, 5 min and 45 cycles of two steps: 95 C, 15 s and 60 C, 30 s. Relative quantification of target gene levels was performed by comparing DCt as described elsewhere [15,16].…”
Section: Cell Culture and Treatmentsmentioning
confidence: 99%
“…The activation and differentiation of fibroblasts into apoptosisresistant, ECM-producing myofibroblasts is a critical factor towards the development of IPF. The accumulation of myofibroblasts within pathologic lesions called fibroblast foci (FF) is a hallmark of IPF lungs, and their fatal apoptosis-resistance promotes their expansion and the consecutive exaggerated ECM deposition in IPF lungs [43,234,235]. Transforming growth factor-beta (TGF-β) is a major stimulus of ECM production in fibroproliferative diseases [236].…”
Section: Adaptive Er Stress In Mesenchymal Cells Of Ipf Lungsmentioning
confidence: 99%
“…In conclusion, a cytoprotective (adaptive) ER stressresponse takes places in contractile protein-expressing myofibroblasts, presumably in order to restore and maintain ER proteostasis under conditions of elevated ECM protein production [232,233,238], and maybe also to allow the continuous production of various survivalrelated proteins, such as survivin, PI3Kγ, and members of the inhibitor of apoptosis (IAP) protein family which maintain the apoptosis-resistance of myofibroblasts and which all have been reported to be upregulated in myofibroblastic cell populations in experimental lung fibrosis and IPF in vivo [234,235,249].…”
Section: Adaptive Er Stress In Mesenchymal Cells Of Ipf Lungsmentioning
confidence: 99%